Spectral Response Surfaces and the Ringing Response of Offshore Structures - Suastika, I Ketut (UI Scholars Hub, 2008)
A method, called spectral response surface method, is proposed for the study of the ringing phenomenon of offshore structures. Newman’s results for diffraction force on a column were reformulated in terms of the frequency components of the ocean surface and their Hilbert transforms. Using a first-order reliability method together with a dynamic model for the structural response, it is straightforward to calculate the ocean surface history most likely to generate an extreme ringing response and the ringing response history.